Genetic programming based drag model with improved prediction accuracy for fluidization systems - Sonolikar, R. R.; Patil, M. P.; Mankar, R. B.; Tambe, S. S.; Kulkarni, B. D. (International journal of Chemical Reactor Engineering, 2017)

Bubble size prediction in gas-solid fluidized beds using genetic programming - Sonolikar, R. R.; Patil, M. P.; Mankar, R. B.; Tambe, S. S.; Kulkarni, B. D. (Current Science, 2018)
The hydrodynamics of a gas-solid fluidized bed (FB) is affected by the bubble diameter, which in turn strongly influences the performance of a fluidized bed reactor (FBR). Thus, determining the bubble diameter accurately is of crucial importance in the design and operation of an FBR. Various equations are available for calculating the bubble diameter in an FBR. It has been found in this study that these models show a large variation while predicting the experimentally measured bubble diameters. Accordingly, the present study proposes a new equation for computing the bubble diameter in a fluidized bed. This equation has been developed using an efficient, yet infrequently employed computational intelligence (CI)-based data-driven modelling method termed genetic programming (GP). The prediction and generalization performance of the GP-based equation has been compared with that of a number of currently available equations for computing the bubble diameter in a fluidized bed and the results obtained show a good performance by the newly developed equation.